Meta-topolin enhanced in vitro regeneration, acclimatization, and genetic stability assessment of regenerated watermelon (Citrullus lanatus Thunb.) - Vasudevan, Venkatachalam; Manickavasagam, Markandan; Banisetti Kalyana Babu, .; Sinniah, Uma Rani (Universiti Putra Malaysia, 2025)
The production of seedless watermelons, primarily through triploid varieties, has surged to meet the growing consumer demand, especially due to the convenience of eating. However, triploid watermelon production is time-consuming, and seed production is tedious. Hence, in vitro propagation has become an alternative, but it faces challenges such as low regeneration response, poor rooting, and low ex vitro establishment. These issues can be addressed by applying aromatic cytokinin meta-topolin (mT) in the regeneration system. Hence, this study aims to investigate the efficacy of meta-topolin (mT) compared to 6-benzyl adenine (BA) for in vitro regeneration and acclimatization of Citrullus lanatus (Thunb.). The effects of aromatic cytokinins BA and mT (0.5, 1.0, 1.5, 2.0, and 2.5 mg/L) on multiple shoot production from cotyledonary node explants of watermelon were evaluated. The highest shoot production (25.24 shoots/explant) was observed with 1.5 mg/L mT, while BA (1.0 mg/L) produced 11.36 shoots/explant. Rooting response in MS medium with indole-3-butyric acid (IBA 0.5 to 2.5 mg/L) showed the best results in IBA 1.0 mg/L with mT-derived shoots (1.5 mg/L), producing 13.33 roots per shoot, compared to 5.62 roots per shoot from BA-derived shoots (1.0 mg/L). After four weeks of acclimatization, mT-derived plants had a 97% survival, while BA-derived plants had 84%. Additionally, mT-derived plants had significantly higher photosynthetic pigments (chlorophyll a (9.2%), b (11.3%), and carotenoids (29.1%)). RAPD and SCoT markers confirmed the genetic stability of the regenerated plants. This research will aid in developing high-quality planting material to produce commercial triploid watermelon plants.